An income-reflective scalable energy level transition system for low/middle income households. (February 2019) - Monyei, Chukwuka G.; Oyedele, Lukumon O.; Akinade, Olugbenga O.; Ajayi, Anuoluwapo O.; Ezugwu, Absalom E.; Akpeji, Kingsley O.; Viriri, Serestina; Adewumi, Aderemi O.; Akinyele, Daniel; Babatunde, Olubayo M.; Obolo, Michael O.; Onunwor, Joshua C.
Highlights: Energy poverty must go beyond access to address electricity mobility. Structured ownership of electrical appliances can improve comfort levels. Coordinated appliances ownership can precipitate economic productivity. Electricity billing must be progressive and just. Abstract: In mitigating against energy poverty in Nigeria, research interest has focused mainly on electricity access and reduced electricity bills for low/medium income households. However, energy poverty in the global south is not only a problem of access but also of mobility which plays a crucial role in the economic productivity of a country. The need therefore arises for a scheme that guides low/medium income level households in increasing ownership of electrical appliances in a way that will improve their quality of life at the least-cost possible. Such a scheme is expected to address a prevailing challenge of poor satisfaction from the utilization of electrical appliances commonly observed with low/medium income households to achieve comfort, using Nigeria as a test case. This paper thus proposes a progressive system of electrical appliance ownership for low/medium income households in Nigeria for improved comfort. Furthermore, this paper advances discussions on building comfort by establishing the relationship between household comfort and economic output for Nigeria. The proposed system and the results obtained find relevance in developing countries especially in sub-Saharan Africa and developing Asia for improving household comfort, mitigating poverty and precipitating economic growth.